The Basis and Advances in Clinical Application of Cytomegalovirus-Specific Cytotoxic T Cell Immunotherapy for Glioblastoma Multiforme - Daei Sorkhabi, Amin; Sarkesh, Aila; Saeedi, Hossein; Marofi, Faroogh; Ghaebi, Mahnaz; Silvestris, Nicola; Baradaran, Behzad; Brunetti, Oronzo (Frontiers in Oncology, 2022)
A high percentage of malignant gliomas are infected by human cytomegalovirus (HCMV), and the endogenous expression of HCMV genes and their products are found in these tumors.HCMV antigen expression and its implications in gliomagenesis have emerged as a promising target for adoptive cellular immunotherapy (ACT) strategies in glioblastoma multiforme (GBM) patients. Since antigen-specific T cells in the tumor microenvironments lack efficient antitumor immune response due to the immunosuppressive nature of glioblastoma, this method relies on in vitro expansion of CMV-specific CD8+ T cells employing immunodominant HCMV antigens. Given the fact that several hurdles remain to be conquered, recent clinical trials have outlined the feasibility of CMV-specific ACT prior to tumor recurrence with minimal adverse effects and a substantial improvement in median overall survival (OS) and progression-free survival (PFS). This review discusses the role of HCMV in gliomagenesis, disease prognosis, and recent breakthroughs in harnessing HCMV-induced immunogenicity in the GBM tumor microenvironment to develop effective CMV-specific ACT.